Methicillin-resistant staphylococcus aureus bacteraemia in adults at Chris Hani Baragwanath academic hospital - Holz, Guillaume Erich (My University, 2019)
Introduction: The advent of methicillin-resistant Staphylococcus aureus (MRSA) has led to poor patient outcomes and longer hospital stays. Initially described as a nosocomial infection, it has now led to the development of community-acquired (CA) strains. This study aimed to describe the differentiation between CA and hospital-acquired (HA) MRSA infections. Methods: A retrospective study was conducted at Chris Hani Baragwanath Academic Hospital in Johannesburg from 1 January 2013 to 31 December 2015. Cases were detected utilising the National Health Laboratory Service. One hundred adult patients that met the inclusion criteria were included in the study. Descriptive statistics was used using the Pearson chi-squared test and a p value of less 0.05 with a confidence interval of 95% was used as statistically significant. Results: Seventy-seven cases were HA, 5 cases were CA and 18 cases were healthcare-associated (HCA). The all-cause mortality was not statistically different between the three groups, but the all-cause mortality was higher in HIV positive patients (61% vs 38%, p value <0.05). Forty-two of 43 cases in the surgical department were HA (97.7% vs. 2.3%); 4 of 5 cases of CA-MRSA and all 18 cases of HCA-MRSA were medical patients. Thirty-nine patients (39 %) were admitted to the intensive care unit. Fifty-seven patients (57%) were HIV-positive, and 34 (60%) were on antiretroviral therapy. Soft-tissue (24%) and catheter- associated infections (21%) were the two most common sources of infection in HA-MRSA patients. HA-MRSA had a lower Charlson co-morbidity index compared to both HCA-MRSA and CA-MRSA (3 vs 6 and 6 respectively, p< 0.05). Conclusion: Rates of CA-MRSA infections remain low in our setting compared to international data, but may be underestimated due to the small sample size. While HA-MRSA is common in surgical patients, HCA-MRSA makes up the majority of cases in medical patients, with co-morbidities and previous hospital exposure important determinants.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine. Johannesburg, 2019